Prospek Usaha Penjualan Bubuk Kopi Aman Kuba Di Takengon Kabupaten Aceh Tengah - Hidayah, Irna; Sastri, Sastri (Universitas Gajah Putih, 2024)
This thesis is the result of research and discussion. The problem identification in this research is what are the business prospects for selling Cuban Safe Coffee powder in Takengon, Central Aceh Regency. And the aim of this research is to determine the business prospects for selling Safe Cuban coffee powder in Takengon, Central Aceh Regency. The benefit of this research is to develop good knowledge and apply the knowledge that has been obtained during the course. Information and references for those selling Safe Cuban Takengon coffee powder as well as a wealth of knowledge. The scope of this research is to analyze the business prospects for selling Aman Kuba coffee powder in Takengon, Central Aceh Regency within the next 5 years. The respondents/informants in this research were 5 owners and employees of CV Aman Kuba Takengon. Data collection was carried out by observation and interviews. This research is quantitative research. The data analysis method uses the least square method with the formula Y=a+bX. From the research results, it was found that sales of Aman Kuba coffee powder in 2018 amounted to IDR 122,500,000, in 2019 it amounted to IDR 168,000,000, in 2020 it amounted to IDR 143,000,000, in 2021 it amounted to IDR 144,000,000, and in 2022 it amounted to IDR 164,000. 000. The results of the discussion obtained from the equation Y = Rp. 148,300,000 + Rp. 5,900,000x, shows that CV coffee powder sales. Aman Cuba has a fixed (constant) sales value of Rp. 148,300,000 and the sales change value (coefficient) b > 0 or positive, namely Rp. 5,900,000. The estimated sales results for Aman Kuba coffee powder using the smallest quadrant method in 2023 are estimated at Rp. 166,000,000,-. In 2024 it will be 171,900,000.-. In 2025 it will be Rp. 177,800,000,-. In 2026 it will be IDR. 183,700,000,-. And the estimated sales of coffee powder in 2027 is IDR. 219,600,000,-. Thus, this value shows the sales of CV coffee powder. Aman Cuba has very good prospects in the future.